Analisis Komunikasi Organisasi Terkait Penanganan Pelanggaran Pilkada 2024 Oleh BAWASLU Kabupaten Pasuruan - Wiwik Maulidah; Moh. Edy Marzuki (Majelis: Jurnal Hukum Indonesia, 2025)
This study examines organizational communication within the General Election Supervisory Body (Bawaslu) of Pasuruan Regency in handling violations during the 2024 Regional Elections (Pilkada). Using a qualitative case study approach, data were obtained through in-depth interviews, observation, and documentation involving Bawaslu members, technical staff, and the Integrated Law Enforcement Center (Gakkumdu). The results show that vertical and horizontal communication flows are generally effective in supporting internal coordination and violation handling, despite challenges such as limited human resources, high workloads, and inter-agency coordination gaps. To address these, Bawaslu strengthens internal meetings, leverages digital media, provides technical training, and enhances external collaboration and public outreach. The study concludes that effective organizational communication significantly improves election monitoring performance and offers insights for communication strategies in other supervisory bodies.To address these issues, Bawaslu has taken several proactive steps. These include strengthening internal meetings to improve coordination and decision-making, leveraging digital media for more efficient communication and reporting, providing technical training to staff to enhance their skills in violation detection and reporting, and fostering stronger collaboration with external agencies such as Gakkumdu for coordinated law enforcement. Additionally, Bawaslu has focused on improving public outreach through social media campaigns to increase awareness of the electoral process and violations. The study concludes that effective organizational communication significantly improves election monitoring performance and offers insights for communication strategies in other supervisory bodies. It recommends that other institutions facing similar challenges in managing complex, multi-agency processes adopt similar strategies to improve both internal and external communication for more efficient operations and outcomes.